Hambatan Terhadap Adopsi Internet banking: Studi Kualitatif Pada Nasabah OCBC NISP - , ARLAN PRATAMA NAPITUPULU, BM Purwanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Internet banking distribution channel has proliferated recently for individual and corporate users. This research purpose is to identify critical factors that hinder internet banking adoption among corporate users. This is an exploratory research that refers to Rotchanakitumnuai and Speece (2003)âs research âBarriers to Internet banking adoption: a qualitative study among corporate customers in Thailandâ. The researcher conducted in- depth interview with person-in-charge of financial decision making from each company. Those companies were classified into two categories